Corporate Governance, Earnings Management dan Kinerja Perbankan di Indonesia - Made Ratih Baskaraningrum (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACT            The purpose of this research is to investigate the concept of the importance of the role of good corporate governance in the banking industry in Indonesia. Specifically, this study intends to examine whether good corporate governance plays a role in improving company performance, especially by limiting earnings management practices. This study focuses on banking companies in Indonesia that are listed on the Indonesia Stock Exchange (IDX). Determination of company samples in this study was carried out by purposive sampling method, with the criteria of banking companies listed on the Indonesia Stock Exchange during the 2014-2016 period. The data collection method used in this study was the method of documentation study. The data analysis method used is Path Analysis.The results of the Square Multiple Correlation for earnings management amounted to 0.795 and banking performance was 0.860, so for earnings management variables influenced by managerial ownership, institutional ownership, the size of the independent board of commissioners, the audit committee amounted to 79.5%. While banking performance variables are influenced by managerial ownership, institutional ownership, board of commissioners size, the proportion of independent commissioners, audit committees and earnings management is 86%. Empirical benefits in research are about the application of corporate governance, earnings management and financial performance in the banking industry in Indonesia. The practical benefits in this study can provide benefits for companies in the application of appropriate corporate governance and benefits for investors who invest their capital in the company and can also be taken into consideration for companies to reduce profit management in the company so as to improve banking performance in Indonesia.